2011
DOI: 10.1016/j.physbeh.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Depression and altered serum lipids in cynomolgus monkeys consuming a Western diet

Abstract: Depression and altered serum lipids in cynomolgus monkeys on a Western diet. Research over the past 15 years has suggested a high comorbidity of depression and coronary heart disease (CHD). However the mechanisms responsible for this relationship are poorly understood. This study was designed to examine the relationships between depressive behaviors and concentrations of circulating lipids and lipid signaling molecules that may be common to both CHD and depression in a cohort of cynomolgus monkeys (Macaca fasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…For this reason we examined coronary artery atherosclerosis extent in monkeys that had, or had not exhibited depressive behavior in the previous 4 years. We found that depressed monkeys had four times the atherosclerosis in their coronary arteries as their nondepressed counterparts (Shively et al, 2009; Shively et al, 2008; Chilton et al, 2011). …”
Section: Comorbidity Of Depression and Coronary Artery Atherosclermentioning
confidence: 69%
“…For this reason we examined coronary artery atherosclerosis extent in monkeys that had, or had not exhibited depressive behavior in the previous 4 years. We found that depressed monkeys had four times the atherosclerosis in their coronary arteries as their nondepressed counterparts (Shively et al, 2009; Shively et al, 2008; Chilton et al, 2011). …”
Section: Comorbidity Of Depression and Coronary Artery Atherosclermentioning
confidence: 69%
“…Careful parsing of behavior data indicated that HFD markedly decreased attention to testing (Reyes, 2014). HFD precipitates depressive behaviors in macaques, (Chilton et al, 2011, Shively et al, 2008), and cognitive impairment in rodents (Pistell et al, 2010, White et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Dom: dominant animals; Sub: subordinate animals; R: response; Dex: dexamethasone; ACTH: adrenocorticotropin hormone; CRH: corticotrophin-releasing hormone; P4: progesterone; ovx: ovariectomized; CSF: cerebrospinal fluid; HVA: homovanillic acid; 5-HT 1A : Serotonin 1A receptor; BP: binding potential; D2: dopamine receptor D2; TPC: total plasma cholesterol; HDL-C: high density lipoprotein cholesterol. Sources: Chilton et al, 2011; Grant et al, 1998; Hamm et al, 1983; Kaplan et al, 2002; Kaplan et al, 2009; Morgan et al, 2000; Riddick et al, 2009; Shively and Clarkson, 1994; Shively et al, 1995; Shively et al, 2003; Shively et al, 2006; Willard et al, 2009; Willard et al, 2011. …”
Section: Fig A1mentioning
confidence: 99%